Study of Thematic and Terminological Transformation of Collections of Scientific Articles in Interdisciplinary Fields of Knowledge - Fedorets, O. V.; Soloshenko, N. S. (Automatic documentation and mathematical linguistics, 2024)
This paper presents the methodology of the quantitative study of the dynamics of changes in the thematic structure of collections and vocabulary of terms that were aimed at selecting documents into thematic collections, creating thematic (classification and subject) profiles of these collections in different chronological periods and a comparative analysis of these profiles. The profiles are treated as descriptive sets, with TF-IDF used as the keyword weight. The methodology is tested in two collections, “Robotics and Robotic Systems” and “Intelligent Systems, Artificial Intelligence, and Machine Learning.”